2013
DOI: 10.5535/arm.2013.37.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medial Branch Block in Chronic Facet Joint Pain for Osteoporotic Compression Fracture: One Year Retrospective Study

Abstract: ObjectiveTo evaluate the outcomes of medial branch block in facet joint pain for osteoporotic compression fracture and utilize multiple regression, the relationship between their impact on treatment outcome and other factor, such as the radiologic finding, clinical parameters was analyze.MethodsFifty-three patients with axial back pain from osteoporotic compression fracture were enrolled. The clinical outcomes were measured by Verbal Numeric Rating Scale (VNS) and Oswestry Disability Index (ODI) before treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
19
0
2
Order By: Relevance
“…These studies raised ardent debates about the effectiveness of vertebroplasty. Another concern is that some OVCFs patients still have back pain after vertebroplasty [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies raised ardent debates about the effectiveness of vertebroplasty. Another concern is that some OVCFs patients still have back pain after vertebroplasty [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that pains associated with OVCFs may arise not just from vertebral body but also from posterior elements [ 7 ]. Therefore, facet blocking (FB) and medial branch blocking would be beneficial for alleviating back pain associated with OVCFs [ 8 , 9 ]. A prospective study showed that PVP produced better pain relief than FB in the short term, but the difference in pain relief between these two techniques was insignificant in the long term (1 month to 12 months) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pain improvement rates after facet blocks or an medial branch block in patients with back pain has been reported in the range of 29-60% in the literature [37]. Park et al reported a satisfaction level of "excellent" or "good" 12 months after the first injection in 78.9% of the patients with osteoporotic spinal compression complaining of persistent low back pain [38]. In the series of Heui Seung Lee and the study of Kim et al, 69.6% and 70% of the patients have benefitted from a medial branch block for their back pain, respectively [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…NB ranks higher probability than PKP and PVP on acute/subacute OVCFs in short and long term, respectively. Several studies showed numerous nerve block of successful treatment in OVCFs patients, such as facet joint block for thoracolumbar or lumbar axial pain, bilateral or unilateral hip pain, and referred pain of the low extremities, [ 59 ] only facet joint block, [ 3 , 60 ] PVP with facet joint block [ 12 , 61 ] or medial branch block of the facet joint for thoracic or lumbar vertebral bodies, [ 62 ] gray ramus communicans nerve block in thoracic and lumbar spine, [ 63 ] nerve-root injections for thoracic or lumbar radiculopathy, [ 64 ] L2 spinal nerve block for acute/subacute midlumbar compression fracture, [ 28 ] and radiofrequency resulted in short-term or long-term pain relief. [ 19 , 65 ] Nerve block is an option in treating painful OVCFs in the AAOS Clinical Practice Guideline, [ 13 ] but does not restore vertebral height or reverse kyphotic deformity.…”
Section: Discussionmentioning
confidence: 99%